Accuracy of clinical scoring systems for the diagnosis of tuberculosis meningitis in a case mix of meningitides a retrospective cohort study - Yahia Z. Imam (9401836) (2020)
Background Tuberculosis meningitis (TBM) is elusive to diagnosis. Two widely used clinical scores are the Thwaites diagnostic score (TDS) and The Lancet Consensus score (LCS). We aim to evaluate the accuracy of these scores in a retrospective cohort of meningitis patients. Methods A retrospective review of all meningitis cases admitted to a tertiary center in a 7-year period. The primary outcome was the sensitivity and the specificity of a preset cutoff on the TDS and the LCS and finding the best cutoff value with optimum sensitivity and specificity using Receiver operating characteristic (ROC) curve analysis. Results We included 156 cases of meningitis; 80 TBM and 76 controls (other meningitides). Seventy-eight (97.5%) of TB cases were suggestive of TBM compared to 45(59.2%) of controls (p < .001) using the TDS. Sensitivity was 97.5% and specificity was 40.8%. The PPV was 63.4% and the NPV was 93.9%. The area under the ROC curve (AUC) was 0.80 (0.73–0.87 at 95% CI). When calculated for bacterial meningitis vs TBM a cutoff of 4 showed excellent sensitivity (93%) and specificity (96%). AUC =0.96 (0.89–1.00 at 95% CI). While for the LCS, 67 (83.3%) were suggestive of TBM vs. 11 controls (14.5%) (p < .001). Sensitivity was 83.8%, specificity was 85.5%, and PPV and NPV were 85.9% and 83.3% respectfully. The AUC was 0.93 (95% CI 0.89–0.97). Conclusion The TDS performs best in differentiating bacterial meningitis from TBM and has a good negative predictive value. The LCS has good sensitivity and specificity in differentiating TBM from others forms of meningitides. Other Information Published in: Journal of the Neurological Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jns.2020.116979